Clinico-investigation on epidemiological study in 119 Indian cases of melasma - Pangti, Rashi; Mendiratta, Vibhu; Chander, Ram; Malik, Meenu (International Journal of Research in Dermatology, 2020)
Background: Melasma, a multifactorial disease, constitutes the most common facial melanosis in Indian population. Methods: 119 cases of melasma aged 18 years or above were enrolled. Detailed history, examination and laboratory investigations were done. Results: 20 (16.8%) were males and 99 (83.2%) females. Mean age was 35.25 years. Disease duration was more than 1 year in 102 (85.7%), 6 months to 1 year in 10 (8.4%) and less than 6 months in 7 (5.9%). 22 (18.49%) had occupation-related increased duration of sun-exposure 19 (86.3%) or heat-exposure 3 (13.6%). 79 (66.4%) had skin type IV, 26 (21.8%) type III, 14 (11.8%) type V. Centrofacial was commonest distribution pattern in 87 (73.1%), malar in 30 (25.2%), mandibular in 2 (1.7%). Mean duration of daily sun-exposure was 53.36 minutes (male-124.75, female-38.94). Mean Melasma Area and Severity Index (MASI) score was 11.602. There was significant association between MASI and skin type (p<0.001). Other etiological factors were: Oral Contraceptive Pills (OCPs) use in 17 (17.17%), melasma during pregnancy in 39 (39.4%), family history of melasma in 24 (20.2%), hair dye use in 66 (55.5%), cosmetics use in 19 (16%), mustard oil use in 31 (26.1%), mustard oil along with other oil(s)’ use in 39 (32.8%). Laboratory investigations revealed anemia in 60 (50.42%), dyslipidemia in 73 (61.34%), abnormal thyroid function test in 26 (21.85%), serum vitamin B12 deficiency in 35 (29.4%) and vitamin D deficiency in 94 (79%). Conclusions: Higher skin phototypes should be cautious about general measures and associated risk factors (hair dye/oils, cosmetics). Increased daily sun-exposure, OCPs use, pregnancy, thyroid disorders are risk factors. Housewives and indoor occupations should be advised physical sunscreens for protection against infra-red radiation. Anemia, dyslipidemia, thyroid dysfunction, vitamin D and B12 levels can be assessed although their exact role in perpetuating/precipitating melasma needs further studies